Advancements and Applications of Quantitative PCR (qPCR) in Plant Science: A Comprehensive Review (Journal of Bio-Science, 2026)
Quantitative PCR (qPCR) has become a cornerstone of modern plant science, offering high-resolution quantification of nucleic acids with exceptional sensitivity and accuracy. Its diverse applications span gene expression profiling, rapid pathogen diagnostics, GMO verification, and the analysis of plant responses to environmental stressors. This review explores the evolving landscape of qPCR in plant research, spotlighting cutting-edge developments, refined methodologies, and emerging trends shaping future directions.J. Bio-Sci. 33(2): 87-94, 2025